The Influence of Leadership Style, Organizational Commitment, and Organizational Culture on Managerial Performance at PT POS Indonesia (Persero) Cirebon Branch - Dwi Ratna Sari; Kartono Kartono (UNIVED Press, 2024)
This study aims to determine the effect of leadership style, organizational commitment, and organizational culture on managerial performance at PT POS Indonesia (Persero) Cirebon Branch. The population in this study were 160 employees of PT POS Indonesia (Persero) Cirebon Branch. The sampling technique in this study uses probability sampling. The sample used was 62 employees. The method in collecting this data used a questionnaire, while the method in this study used the method of multiple linear regression analysis. Based on the results of data analysis shows that: 1) Leadership style has a negative and significant effect on managerial performance. 2) Organizational commitment has a positive and significant effect on managerial performance. 3) Organizational Culture has a positive and significant effect on managerial performance. 4) Leadership style, organizational commitment, and organizational culture simultaneously affect managerial performance at PT POS Indonesia (Persero) Cirebon Branch. The magnitude of the influence of leadership style, organizational commitment, and organizational culture together on managerial performance at PT POS Indonesia (Persero) Cirebon Branch by 56.9% while the remaining 43.1% is influenced by other factors not examined.